STRATEGI BERBASIS AJARAN BUDDHA DALAM PENANGGULANGAN STUNTING PADA IBU HAMIL - Betaria; Ani; Theresia Halim Nuriani; Lisniasari; Lamirin (Jurnal Genta Mulia, 2026)
Stunting is a chronic nutritional problem that has a serious impact on children's physical growth and cognitive development, and contributes to the ongoing cycle of poverty. In Indonesia, the prevalence of stunting is still high, especially in early life which is greatly influenced by the health and nutritional conditions of pregnant women. This study aims to formulate a stunting management strategy based on the teachings of the Tripiṭaka which emphasizes a holistic approach through aspects of nutrition, mental health, spirituality, and social support. This study uses a qualitative method with a literature study approach, Tripiṭaka text analysis, and in-depth interviews with medical personnel, religious figures, and therapists. The results of the study show that the teachings in the Tripiṭaka such as Ussūrabhaṭa Sutta And Putamamsa Suttaemphasizes the importance of healthy eating and mindful eating, while Dhammapada And Nibbāna Sutta underlines the role of the mind in maintaining mental balance.Santuṭṭhi Sutta And Sigalaka Sutta emphasizes the importance of inner satisfaction and harmonious social relations in creating an environment that supports maternal health. Field findings confirm that mental imbalance in pregnant women, low nutritional literacy, and minimal social support are the main factors causing stunting. Integration of Buddhist values ​​in public health programs shows increased awareness and positive behavioral changes. This study concludes that the Tripiṭaka-based approach can be a contextual and sustainable strategy in preventing stunting, and recommends cross-sector collaboration in its implementation to support a healthy and quality generation.